Designing MnO2 & carbon composite porous nanofiber structure for supercapacitor applications. (20th December 2017) - Ju, Jingge; Zhao, Huijuan; Kang, Weimin; Tian, Nana; Deng, Nanping; Cheng, Bowen
Abstract: In this study, the MnO2 & carbon composite porous nanofibers (CPNF) were prepared via electro-blown spinning and in-situ hydrothermal synthesis. The MnO2 nano-sheets were uniformly growing on carbon skeleton and filling in honeycomb-like carbon porous nanofibers, and the clear CPNFs were formed. The different hydrothermal parameters including the mass ratios of honeycomb-like porous carbon nanofiber and potassium permanganate, hydrothermal times and temperatures were discussed to obtain optimizing reaction conditions. The CPNFs were investigated by scanning electron microscopy (SEM), transmission electron microscope (TEM), energy dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and low temperature nitrogen adsorption, respectively, and the supercapacitor performance of CPNF was preliminary tested. The discharge capacity was 421.5 F g −1 at 0.5 A g −1, and it retained ∼81.2% after 3000 cycles at the current densities of 1.0 A g −1 . Moreover, this CPNF owned special structure and a great industrialization potentiality which could realize the applications in absorption and catalyst fields.